2002
DOI: 10.1161/01.cir.0000031160.86313.24
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Mechanisms of Acquired QT Prolongation and Torsades de Pointes in Rabbits With Chronic Complete Atrioventricular Block

Abstract: Background-The ionic basis of acquired QT prolongation and torsade de pointes (TdP) unrelated to drugs is not fully understood. Methods and Results-We created a rabbit model with chronic complete atrioventricular block (AVB) (nϭ34), which showed prominent QT prolongation (by 120%), high incidence of spontaneous TdP (71%), and cardiac hypertrophy. Patch-clamp experiments were performed in left ventricular myocytes from 9 rabbits (8 with TdP, 1 without TdP) at Ϸ21 days of AVB and from 8 sham-operated controls wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 21 publications
6
68
1
Order By: Relevance
“…These findings were based on canine and rabbit models of chronic complete AV block that showed reduction in I Kr and I Ks , and altered L-type Ca 2+ current, with other currents (inward Na + current, transient outward K + current and inward rectifier K + current) remaining normal (15,16,18). The antiarrhythmic drugs, dofetilide and azimilide, produced similar electrophysiological and proarrhythmic effects on canine hearts (19).…”
Section: Mechanism Of Tdp In Complete Av Blockmentioning
confidence: 91%
See 1 more Smart Citation
“…These findings were based on canine and rabbit models of chronic complete AV block that showed reduction in I Kr and I Ks , and altered L-type Ca 2+ current, with other currents (inward Na + current, transient outward K + current and inward rectifier K + current) remaining normal (15,16,18). The antiarrhythmic drugs, dofetilide and azimilide, produced similar electrophysiological and proarrhythmic effects on canine hearts (19).…”
Section: Mechanism Of Tdp In Complete Av Blockmentioning
confidence: 91%
“…Mechanistically, it has been reported that during bradyarrhythmias, downregulation of the repolarizing currents -rapid and slow delayed rectifier K + currents (I Kr and I Ks , respectively) -results in QT interval prolongation and TdP (15)(16)(17)(18). These findings were based on canine and rabbit models of chronic complete AV block that showed reduction in I Kr and I Ks , and altered L-type Ca 2+ current, with other currents (inward Na + current, transient outward K + current and inward rectifier K + current) remaining normal (15,16,18).…”
Section: Mechanism Of Tdp In Complete Av Blockmentioning
confidence: 99%
“…Interestingly, Brooksby et al (5) have shown that the electrical remodeling related to cardiac hypertrophy was restricted to a decrease in I K1 current density with no difference in the resting potential level of cardiomyocytes from control and spontaneously hypertensive rats. The fewer electrophysiological studies available in the literature related to volume-overload induced cardiac hypertrophy showed a decrease in I K (50,56) but an increase in I K1 without any change in I to (56).…”
mentioning
confidence: 87%
“…Moreover, several similarities have been found between experimental models of atrioventricular block-induced torsades de pointes and specific forms of human congenital long QT syndrome. Frequent episodes of spontaneous torsades de pointes during day and night, abnormal QTU complex, and reduction of both IKr and IKs in a rabbit atrioventricular block model (Tsuji , 2002) closely resemble the clinical characteristics of the malignant form of human congenital long QT syndrome caused by double mutation of HERG and KCNQ1. An enhanced susceptibility to acquired torsades de pointes, the adrenergic dependence of torsades de pointes, the typical T-wave patterns during prolonged QT intervals and the reduction of IKs in dog with chronic atrio-ventricular block closely resemble the clinical characteristics of the LQT1 or LQT5 form of human congenital long QT syndrome.…”
Section: Genetic Bases Of Atrio-ventricular Block-induced Torsades Dementioning
confidence: 65%
“…This association has been extensively evaluated in animal studies. Tsuji et al reported the results obtained in a rabbit model with atrio-ventricular block induced by injection of formaldehyde into the atrio-ventricular node (Tsuji, 2002). These rabbits received ventricular pacing support after atrio-ventricular block induction.…”
Section: Electrical Remodelling During Atrio-ventricular Blockmentioning
confidence: 99%